Larangan Riba Dalam Teks dan Konteks (Studi Atas Hadits Riwayat Muslim Tentang Pelaknatan Riba) - Muhammad Tho’in (Jurnal Ilmiah Ekonomi Islam, 2016)
Usury is additions which hinted at by people who have treasure to those who borrow their wealth (money) because of postponement payment promise by the borrower of a predetermined time. Usury is divided into two kinds of Nasi’ah usury and Fadhl usury. Threats to the behavior of usury is likened to a drunken man who can not stand but as stands one whom possessed devil because (madness), will be incorporated into the fires of hell and eternal forever, people who do not leave usury will be fought by Allah and His messenger It will be categorized as infidels, get anathema Prophet. Lessons of usury restriction can made man like helping each other, closing the door on the action of disconnecting good relationship fellow men, glorifies work, and do not harm those who are in distress. Allah and the Prophet cursed anyone who involved in such practices without exception. Usury behavioral contexts that society do today which include banking transactions primarily conventional banking, insurance transactions, sale and purchase transactions on credit, and much more. Keywords: Hadith, the prohibition of usury, text and context